2014
DOI: 10.1152/jn.00802.2013
|View full text |Cite
|
Sign up to set email alerts
|

Monkeys time their pauses of movement and not their movement-kinematics during a synchronization-continuation rhythmic task

Abstract: A critical question in tapping behavior is to understand whether the temporal control is exerted on the duration and trajectory of the downward-upward hand movement or on the pause between hand movements. In the present study, we determined the duration of both the movement execution and pauses of monkeys performing a synchronization-continuation task (SCT), using the speed profile of their tapping behavior. We found a linear increase in the variance of pause-duration as a function of interval, while the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Praamstra and Pope (2007) described a reduction in post movement beta synchronisation in Parkinson patients who experience motor and perceptual timing difficulties, both caused by an aggravated dopaminergic system (Jahanshahi et al, 2010). Moreover, the hypothesis of motor inhibition for timing is congruent with observation that monkeys in the synchronization-continuations task time the pauses and not the kinematics of their movements (Donnet et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Praamstra and Pope (2007) described a reduction in post movement beta synchronisation in Parkinson patients who experience motor and perceptual timing difficulties, both caused by an aggravated dopaminergic system (Jahanshahi et al, 2010). Moreover, the hypothesis of motor inhibition for timing is congruent with observation that monkeys in the synchronization-continuations task time the pauses and not the kinematics of their movements (Donnet et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, dynamical synchronization processes during cooperative behavior have been described in several empirical examples during joint action tasks in humans, where individuals adjust their own behavior to that of another person in time (Schmidt, Fitzpatrick, Caron, & Mergeche, 2011;Sebanz & Knoblich, 2009), under both intended and unintended conditions (Issartel, Marin, & Capodi, 2007;Richardson, Marsh, & Schmidt, 2005;Schmidt, Fitzpatrick, Caron and Mergeche, 2011). A recent behavioral study (Donnet, Bartolo, Fernandes, Cunha, Prado, & Merchant, 2014) has shown that macaque monkeys use an explicit strategy to perform a synchronization-continuation task, in which they control the duration of their tapping pauses to properly perform the task. Together with the results of other experiments by the same group (Merchant & Honing, 2014;Merchant, Zarco, P erez, Prado, & Bartolo, 2011), this suggests that macaque monkeys show some of the behavioral traits that define rhythmic entrainment.…”
Section: Synchronization and Temporal Adaptationmentioning
confidence: 99%
“…Furthermore, LFPs are a local version of the EEG that is not distorted by the meninges and the scalp and that is a signal that provides important information about the input-output processing inside local networks [97]. Now, the analysis of putaminal LFPs in monkeys performing the SCT revealed an orderly change in the power of transient modulations in the gamma (30-70 Hz) and beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) as a function of the duration of the intervals produced in the SCT (figure 3) [98]. The burst of LFP oscillations showed different preferred intervals so that a range of recording locations represented all the tested durations.…”
Section: Neurophysiology Of Rhythmic Behaviour In Monkeysmentioning
confidence: 99%